The effectiveness of using flipbook maker to improve the chemistry learning outcomes of senior high school students - Nova Irawati Simatupang; Elferida Sormin (Pascasarjana Universitas Negeri Medan, 2020)
This research was conducted by applying a flipbook maker to improve student chemistry learning outcomes on the subject of hydrocarbons. The aims of this study was to determine the effectiveness of the use of flipbook maker to improving student chemistry learning outcomes. The use of this flipbook can increase students interest in learning chemistry which also affects the increase in students chemistry learning outcomes. The population in this research were all students of XI senior high school (SHS) Darussalam Tangerang. The sample of the study was students of XI MIA 1 consisting of 32 students. The sample was selected by the purposive sampling techniqe. The instrument used was multiple choice questions consisting of 20 items. Based on the pre requisite test, the data obtained were normally distributed with sig = 0.094 > 0.05 and homogeneous with sig = 0.014 > 0.05. Hypothesis testing is done using one sample t-test with significance level of 0.05 using the SPSS. From the research results obatined tcount (15.346) > ttable (1.670) and significant value of 0.000 < 0.05. Based on this, it can be concluded that use flipbook makers is effective to improving student chemistry learning outcomes. Keywords: Chemistry; flipbook-maker; hydrocarbon; learning outcomes